ENAMEL HYPOPLASIA: ETIOLOGY, PATHOGENESIS, CLINICAL FEATURES, AND PREVENTIVE STRATEGIES (International journal of medical sciences, 2026)
Enamel hypoplasia is a developmental defect of dental enamel characterized by a quantitative reduction in enamel thickness due to disruption during amelogenesis. It may present as pits, grooves, or generalized thinning of enamel and can affect both primary and permanent dentition. The condition is associated with genetic, systemic, environmental, and nutritional factors. Enamel hypoplasia increases susceptibility to dental caries, dentin hypersensitivity, and aesthetic concerns. This article reviews the etiology, pathogenesis, classification, clinical presentation, diagnosis, management, and preventive approaches of enamel hypoplasia.